Qur’anic Character Values in Indonesia’s Islamic Education Curriculum - Alhamuddin Alhamuddin; Andi Murniati; Towil Akhirudin (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This study examined how character values from thematic Qur’anic surahs were embedded into the Islamic Education Curriculum (PAI) in Indonesia. It addressed the concern that Qur’anic moral teachings were not sufficiently reflected in the formal curriculum, despite the increasing need for character education in schools. A qualitative approach using content analysis was applied to explore selected surahs—Surah Luqman (31:12–19), Al-Hujurat (49:11–13), and Al-Isra (17:23–39)—which emphasized ethical and character-based guidance. These verses were analyzed in relation to the national curriculum components, including core competencies, learning outcomes, and character education objectives. The findings revealed that the surahs contained essential character values such as monotheism (tauhid), respect for parents, humility, honesty, patience, discipline, and social responsibility. While some of these values were partially present in the existing curriculum, their integration lacked depth and coherence. The study concluded that thematic Qur’anic surahs offered a strong foundation for reinforcing character education within the Islamic Education Curriculum. It recommended a more structured and consistent incorporation of Qur’anic character values to enhance the moral development of students in Indonesian schools